Environmental regulation, high-quality economic development and ecological capital utilization - Li, Tao; Tian, Wenqian; Zhang, Shitong; Wang, Shuhong (Frontiers in Environmental Science, 2024)
The key to realizing sustainable human development is to improve the utilization of ecological capital. Under the requirements of innovation-driven and green economic development, how to formulate appropriate environmental regulation policies and accurately implement high-quality economic development strategies to promote the utilization of ecological capital has become the focus of theoretical research and practical exploration. This paper examines the effects of environmental regulation, high-quality economic development, and the interaction term between the two on ecological capital utilization using a fixed-effects model based on panel data for 30 provincial-level political regions (excluding Tibet) in China from 2008 to 2020. The empirical results show that both environmental regulation and economic quality development have a significant positive effect on ecological capital utilization. However, environmental regulation can inhibit technological innovation, which in turn affects economic quality development, and the interaction term between environmental regulation and economic quality development has a significant negative effect on ecological capital utilization. Based on this, the government should enhance environmental regulations while increasing support and technological innovation subsidies for heavily polluting enterprises and new industries to promote high-quality economic development while improving the utilization of ecological capital.